An Argument for the Law of Desire. Issue 4 (1st August 2019) - Barnes, Eric Christian
Abstract: The law of desire has been proposed in several forms, but its essential claim is that agents always act on their strongest proximal action motivation. This law has threatening consequences for human freedom, insofar as it greatly limits agents' ability to do otherwise given their motivational state. It has proven difficult to formulate a version that escapes counterexamples and some categorically deny its truth. Noticeable by its absence in the literature is any attempt to provide an argument for the law of desire – I propose such an argument here. It is noted that Sripada's "divided mind" theory of willpower provides a counterexample to the version of the law of desire my argument defends, but I note that a reformulated version of the law of desire survives this critique. I conclude that there is a serious case for the law of desire, and note the broader implications of this.